Controllership as an instrument to reduce information asymmetry in public companies: a Brazilian public company case study in the port sector. (23rd June 2021) - Pinheiro, Roberto Paveck; Vasconcelos, Ana Lucia Fontes De Souza; Segura, Liliane Cristina; Santos, José Manoel Gatto Dos
This study identifies the characteristics and activities performed in the controllership area of a Brazilian public company in the port sector. The theme is based on the theory of informational asymmetry addressing controllership in the management of internal control and information systems. The methodology uses a qualitative approach, including both an analysis of the literature on the topic and data extracted from documentary analysis of the company's public reports issued by Companhia Docas do Estado de São Paulo (CODESP). The proposed arrangement for a customised structure for the controllership at CODESP adds new responsibilities to the current ones to allow the area to act institutionally, to contribute effectively, and to improve the company's financial management. This study contributes scientifically to the debate on controllership as an instrument in the reduction of fraud risks in the port sector. In an applied way, it has the potential for replicability within the sector. The work presents an interventionist option for the company in the fight against fraud.